The Influence of Mathematical Disposition on The Mathematical Problem-Solving Ability of Fifth-Grade Elementary School Students - Nurlela, Sifa; Yuliyanto, Aan; Nurhasanah, Siti; Mulia, Ajeng Sifa; Ridwan, Reza Muhamad; Nurrahmah, Jamilah (International Conference on Elementary Education, 2025)
This research is based on the importance of mathematical disposition to problem-solving abilities. Learning mathematics’s objectives include cognitive aspects seen in mathematical problem-solving. Mathematical dispositions can show abilities and affective aspects.Problem-solving skills are challenging tasks that require critical and creative thinking, which require a combination of knowledge and skills. Teachers must be able to stimulate students in Learning mathematics by trying to improve mathematical disposition with the material of spatial shapes, namely cubes, and cuboids. This literature review uses an integrative review design to determine the influence of mathematical disposition on problem-solving abilities. A mathematical disposition is a propensity for optimistic thought and behavior. In order to solve challenges, students must be persistent. Students with a high mathematical disposition will be more confident in solving problems. This attitude is an indicator of mathematical disposition. The steps of problem-solving are understanding the problem and planning problem-solving, creating a problem-solving process, and explaining or interpreting the results according to the initial problem. Thus, mathematical disposition can be used to solve students’ mathematical problems.